Typology of rooms with a central terrace system - Jabłońska, Joanna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
Contemporary concert halls with auditoriums over 1800 people, are representatives of a number of innovative spatial solutions. Despite, undutiful layouts variety, most of them origin in plan of Berlin Philharmonic Hall, which was opened in year 1963. Due to differences and similarities observed in elaborated interiors, erected from 70. of XX cent., till beginning of years 2000, in this elaboration there was presented original typology of, so called: vineyard concert halls.